Validity and Reliability of Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) in Indonesia and the Correlation with Quality of Life - Riwanti Estiasari; Yuhyi Fajrina; Diatri Nari Lastri; Syarli Melani; Kartika Maharani; Darma Imran; David Pangeran; Freddy Sitorus (Neurology Research International)
Introduction. Multiple Sclerosis (MS) can affect cognitive function that might interfere with quality of life. Processing speed and memory are the most common area of cognitive impairment. Cognitive evaluation in daily practice is often difficult to be performed since it needs neuropsychological expert and is time-consuming. Brief International Cognitive Assessment for MS (BICAMS) is valid and practical for cognitive evaluation. This study aims to validate BICAMS in Indonesian MS patients and healthy controls (HC) and to analyse the effect of cognitive impairment on quality of life. Methods. BICAMS, which composes Symbol Digits Modalities Test (SDMT), California Verbal Learning Test-Second Edition (CVLT-II), and Brief Visuospatial Memory Test-Revised (BVMT-R), was translated and cross-culturally adapted to Indonesian from the original BICAMS and then administered to 40 Indonesian MS patients and 66 HC matched by sex, age, and education. Test-retest reliability was performed on 16-MS patients and 42 HC. Quality of life was measured using Multiple Sclerosis Quality of Life (MSQOL-54) instrument. Results. The SDMT, CVLT-II, and BVMT-R score in MS patients were significantly lower than those in HC (effect size, r: 0.61, 0.36, and 0.47, respectively). Test-retest reliability for all tests was satisfactory with correlation coefficient for SDMT, CVLT-II, and BVMT-R in MS subjects 0.86, 0.81, and 0.83, respectively. Using 5th percentile of HC score as cut-off, 15% MS subjects had impairment in one test, 27.5% in two tests, and 40% in three tests. BICAMS was moderately correlated with EDSS but was not correlated with disease duration and relapse rate. SDMT score correlated with physical function and physical and mental role limitation. Conclusion. BICAMS is valid and reliable for assessing cognitive function of Indonesia MS patients.